2019
DOI: 10.1111/jan.14245
|View full text |Cite
|
Sign up to set email alerts
|

Educating health professionals for cultural competence in emergency situations: A study protocol for a randomized controlled trial

Abstract: Aims:The current study is aimed at developing a culturally informed education program to increase cultural competence in emergencies among healthcare students and to examine its effectiveness using a randomized controlled trial.Design: This is a mixed-methods study, which comprises two phases: (a) Development of educational intervention to increase cultural competence, based on a review of published scientific literature and primary data collection from qualitative semistructured interviews with key informants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A cultural interpretation of community resilience suggests that the community’s capacity to deal with changes is highly influenced by cultural attitudes, values, and norms. From this point of view, a culturally sensitive approach to emergencies entails a global and local understanding of culture-related expectations and attitudes [ 84 , 85 ]. For example, research in minority communities in Israel during the first wave of COVID-19 showed that keeping social distancing in large, multi-generational households was almost impossible not only due to inadequate space for quarantining but also because shared values make it culturally unacceptable to avoid physical proximity or to send an ill family member away [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cultural interpretation of community resilience suggests that the community’s capacity to deal with changes is highly influenced by cultural attitudes, values, and norms. From this point of view, a culturally sensitive approach to emergencies entails a global and local understanding of culture-related expectations and attitudes [ 84 , 85 ]. For example, research in minority communities in Israel during the first wave of COVID-19 showed that keeping social distancing in large, multi-generational households was almost impossible not only due to inadequate space for quarantining but also because shared values make it culturally unacceptable to avoid physical proximity or to send an ill family member away [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The model was developed by eight emergency medical experts and three nursing experts who specialized in emergency knowledge and skills, teaching methods, scenario simulation, and emergency communication. The training program for the model was designed by two of the authors (YJH and LHZ), based on the available literature in the field [ 20 22 ]. After consulting senior experts in pediatric emergency medicine, BLS education, and hospital training management, the draft content of the model was discussed and revised.…”
Section: Methodsmentioning
confidence: 99%
“…Data was collected between October 2019 and January 2020. For full details about the study protocol, please see Slobodin et al [ 46 ].…”
Section: Methodsmentioning
confidence: 99%